Handbook of Scenario Resources for Inquiry Learning in STEM : IS-IT Learning? Online Interdisciplinary Scenario-Inquiry Tasks for Active Learning in Large, First Year STEM Courses. - Gahan, Lawrence; Lawrie, Gwen; Matthews, Kelly; Adams, Peter; Long, Phil; Kavanagh, Lydia; Weaver, Gabriela; Cusack, Rodney (Australian Learning and Teaching Council (ALTC), 2011)
Handbook containing a compilation of inquiry-based tasks, developed as part of a project that delivered an adaptable model for large, introductory science, technology, engineering and mathematics (STEM) courses with guidelines for shifting passive, content-driven courses to active, inquiry-driven pedagogies within an aligned course curriculum. This was achieved through the introduction of a series of interactive, online Interdisciplinary Scenario-Inquiry Tasks (IS-ITs). By enabling a shift from passive to active learning, this project assisted students to (1) transition to a deeper approach to learning, (2) analyse, synthesise, and evaluate problems via IS-ITs, (3) actively engage in learning, (4) transfer knowledge across traditional disciplinary boundaries, (5) gain an understanding of the interdisciplinary nature of modern science, and (6) increase their enthusiasm for STEM disciplines. A key feature of the new model is that it will benefit students across the full spectrum of abilities and backgrounds. The team has adopted principles developed in another ALTC project Developing and disseminating TEAM SKILLS) which produced a web-based system enabling group management and promoting 'healthy' group function for integration into the IS-IT learning experience. To date a suite of 10 pilot scenarios have been developed and trialled.